Integration of innovative users as source of service innovations - Florian Skiba; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2008)
In this study we research user integration in the German service industry. Goal is to explore the industrial practice with regard to four dimensions of user integration, i.e., why, whom, how, and how successful the service industry integrates to find novel service ideas. Data is collected from a large-scale survey sent out to 2,905 service companies and posted in various user groups related to service innovations. Drawing from data gathered from 301 respondents in our study, we present explorative findings for each distinct dimension of user integration. To better understand the interrelation of these dimensions, we also create a structural equation model using partial least square for estimation of direction and strength of relationships between those. Results show that service companies like companies from other industries actively pursue the development of radical innovations. We find that service companies do not integrate users by random. Instead a service company's level of importance for radical innovation significantly determines both, choice of users integrated as well as choice of integration instruments deployed. In our study we can also show, that many of the beliefs brought forward by service companies for not integrating users cannot be sustained in the light of our findings. We can demonstrate that user contributions provide true value to those companies integrating the latter, and also that using tools which are considered easy and versatile to apply can still have a significant impact on the attractiveness of user ideas.
Keywords: 650